Analysis of the Effect of the Human Development Index, the Open Unemployment Rate on the Poverty Rate in North Sumatra, 2004 – 2022 - Haifa Azalia Pinem; Cinta Marito Simbolon; Uci Aulia Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to analyze the effect of the Human Development Index (IPM) and the Open Unemployment Rate (TPT) on the poverty rate in North Sumatra in the long and short term. The data used in this research is secondary data obtained from the Central Bureau of Statistics from 2004-2022. The analysis used is regression analysis with the Error Correction Model (ECM) method. The tests used in the model are Stationarity Test, R-Square Test, F Test and T Test. The results of this study are that in the long run the Human Development Index (IPM) has a negative and significant effect on the Poverty Rate in North Sumatra while the Open Unemployment Rate (TPT) ) has a positive and significant effect on the Poverty Level in North Sumatra. In the short term the Human Development Index (IPM) and the Open Unemployment Rate (TPT) have a negative and significant effect on the Poverty Rate in North Sumatra.